Swimming as a context for learning number patterns: a study of mathematical connections and anxiety - Kiki Nia Sania Effendi; Leli Nurlaeli; Rafiq Zulkarnaen; Aprianti Nur Alyah (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the effectiveness of learning number patterns in the context of swimming and the relationship between mathematical connection skills and the level of mathematical anxiety of junior high school students in learning number patterns in the context of swimming. This study used a one-group pretest-posttest design with a sample size of 40 eighth-grade students in class VIII B at a junior high school in Telukjambe Timur subdistrict. Data were collected through a mathematical connection ability test and a mathematical anxiety questionnaire. Quantitative data analysis used the effect size formula and Pearson's correlation test to examine the relationship between variables. The results showed that learning number patterns with a swimming context was effective in improving mathematical connection skills and reducing anxiety levels, and there was a significant relationship. This indicates a very strong and positive relationship, where the effectiveness of learning with a swimming context in building mathematical connections is directly proportional to the affective condition of students. Strengthening mathematical connections through a swimming context can be a way to manage students' mathematical anxiety.